Direct-acting oral anticoagulant removal by intraoperative hemoadsorption in CABG and/or single valve surgery: interim analysis of the International Safe and Timely Antithrombotic Removal (STAR) registry - Michael Schmoeckel; Matthias Thielmann; Keti Vitanova; Thomas Eberle; Nandor Marczin; Kambiz Hassan; Andreas Liebold; Sandra Lindstedt; Georg Mächler; Marijana Matejic-Spasic; Daniel Wendt; Efthymios N. Deliargyris; et al. (Journal of Cardiothoracic Surgery)
Abstract Objective Patients on direct-acting oral anticoagulants (DOACs) are at high risk of perioperative bleeding complications. Intraoperative hemoadsorption is a novel strategy to reduce perioperative bleeding in patients on DOACs undergoing non-deferable cardiac surgery. The international STAR-registry reports real-world clinical outcomes associated with this application. Methods The hemoadsorption device was incorporated into the cardiopulmonary bypass (CPB) circuit and active for the duration of the pump run. Patients on DOACs undergoing CABG and/or single valve surgery before completing the recommended washout were included. Outcome measurements included bleeding events according to standardized definitions and 24-hour chest-tube-drainage (CTD). Results A total of 62 patients were included from 7 institutions in Austria, Germany, Sweden, and the UK (mean age 69.9 ± 7.5years, 71% male). Approximately half were on apixaban and the other half was split between rivaroxaban and edoxaban with 21% of patients also on aspirin. Surgery occurred at a median time of 28.9 h since the last DOAC dose with single valve surgery accounting for 2/3 of cases. Mean CPB duration was 118.6 ± 46.4 min. Severe bleeding (UDPB ≥ 3) occurred in 4.8%, and BARC-4 bleeding occurred in 3.2% of the patients. Only one patient (1.6%) required reoperation for bleeding control. The mean 24-hour CTD was 771.3 ± 482.79mL. No device-related adverse events were reported. Conclusions This interim report of the ongoing STAR-registry shows that, in patients on DOAC undergoing non-deferable CABG and/or single valve surgery, the use of intraoperative hemoadsorption is associated with low rates of severe perioperative bleeding complications. Further prospective studies in larger cohorts are needed to validate the efficacy of this method. Clinical registration number ClinicalTrials.gov identifier: NCT05077124.